WELDING ANALYSIS OF GRAY CAST IRON ASTM A48 CLASS 40 USING SMAW - Diah Kusuma Pratiwi; Amir Arifin; Reza Andre Suhada (Asosiasi Peneliti Sriwijaya, 2021)
The mechanical and physical characteristics of gray cast iron are intricately bound to its application as an essential material in manufacturing various goods. SMAW (Shielded Metal Arc Welding) is the most simple and widely used electric arc welding method. In this work, ASTM A48 gray cast iron Class 40 was joining using the SMAW method with the welding position used was 1G or underhand position. The joining used is the Butt Joint using an open Singel V seam with a current of 120A. The joining of Welding was characterized through dye penetrant and hardness tests. Rockwell hardness tests on base metal and heat affected zone reveal that the heat affected zone has the highest hardness value of 56.5 HRC, while the base metal has the lowest hardness value (41 HRC). Graphite, pearlite, and pearlite were all visible in the microstructure study.